On the Debate on Historicism and Anti-Historicism in Deleuze - Antonelli Marangi, Marcelo Sebastián (Revista de Filosofía, 2017)
After having elaborated a Universal History version motorized by desiring production, Deleuze adopted an anti-historicist turn, concentrated on non-historical becomings and made the negative perspectives upon History soar. Within the realm of the debate between those who grant him anti-historicist positions exclusively, and those who endow him a Philosophy of History or a historicist methodology, we intend to shed light on the deleuzian critics to history making use of the difference between History as reality and as discipline. Furthermore, we shall explain the valorization of Philosophy over History based on Deleuze’s conception of event and its time.